Serum neuron-specific enolase as an early predictor of delayed neuropsychiatric sequelae in patients with acute carbon monoxide poisoning. (March 2018) - Cha, YS; Kim, H; Do, HH; Kim, HI; Kim, OH; Cha, K-C; Lee, KH; Hwang, SO
Delayed onset of neuropsychiatric symptoms after apparent recovery from acute carbon monoxide (CO) poisoning has been described as delayed neuropsychiatric sequelae (DNS). To date, there have been no studies on the utility of serum neuron-specific enolase (NSE), a marker of neuronal cell damage, as a predictive marker of DNS in acute CO poisoning. This retrospective observational study was performed on adult patients with acute CO poisoning consecutively treated over a 9-month period. Serum NSE was measured after emergency department arrival, and patients were divided into two groups. The DNS group comprised patients with delayed sequelae, while the non-DNS group included patients with none of these sequelae. A total of 98 patients with acute CO poisoning were enrolled in this study. DNS developed in eight patients. The median NSE value was significantly higher in the DNS group than in the non-DNS group. There was a statistical difference between the non-DNS group and the DNS group in terms of CO exposure time, Glasgow Coma Scale (GCS), loss of consciousness, creatinine kinase, and troponin I. GCS and NSE were the early predictors of development of DNS. The area under the curve according to the receiver operating characteristic curves of GCS, serum NSE, and GCS combined with serum NSE were 0.922, 0.836, and 0.969, respectively. In conclusion, initial GCS and NSE served as early predictors of development of DNS. Also, NSE might be a useful additional parameter that could improve the prediction accuracy of initial GCS.